Case Series of Steroid-Resistant Immune Checkpoint Inhibitor Associated Myocarditis: A Comparative Analysis of Corticosteroid and Tofacitinib Treatment - Wang, Cong; Lin, Jinyi; Wang, Yan; Hsi, David H.; Chen, Jiahui; Liu, Tianshu; Zhou, Yuhong; Ren, Zhenggang; Zeng, Zhaochong; Cheng, Leilei; Ge, Junbo (Frontiers in Pharmacology, 2021)
Background: Immune checkpoint inhibitor (ICI)-associated myocarditis is an uncommon and potentially fatal immune-related adverse event (irAE). Though corticosteroids are recommended as the first-line treatment by current guidelines, patients still have variable responses to it and the guidelines vary significantly in terms of treatment strategies. Objectives: In this study, we performed a retrospective analysis of ICI-associated myocarditis in our hospital to propose a new classification for individualized treatment. Methods: We reviewed detailed records of 24 patients with confirmed ICI-associated myocarditis in our hospital from July 1st, 2019 to April 1st, 2021. Although all the cases in our study received recommended initial corticosteroid treatment according to the guidelines, different responses to corticosteroid were observed during the process of subsequent corticosteroid tapering. Basing on troponin cTnT rebound during corticosteroid tapering, we proposed a new classification of ICI-associated myocarditis that included two subgroups: corticosteroid-sensitive (n=8) and corticosteroid-resistant group(n=16). Results: Compared with corticosteroid sensitive patients, larger doses of corticosteroid, longer period of treatment and higher mortality rate were found in corticosteroid resistant patients. Corticosteroid resistant patients were characterized by more prominent ptosis, muscle weakness, elevated cardiac biomarkers, creatine kinase and hepatic enzymes levels than that in the corticosteroid sensitive patients. Tofacitinib (5mg twice a day) was used in 11 corticosteroid resistant patients and 7 of which recovered from ICI-associated myocarditis, with a promising therapeutic effect. Conclusion: Our new corticosteroid responsiveness classification in patients with ICI-associated myocarditis may help clinicians to apply individualized treatment in this high-risk cohort. In addition, tofacitinib could provide clinical benefits when used early in the corticosteroid resistant patients and provide a new option for the treatment of ICI-associated myocarditis.